Le service civique au service de l’insertion des jeunes Réunionnais·es ? - Florence Ihaddadene (La Nouvelle Revue du Travail)
The French Civic service, a voluntary work status, has been widely promoted on Réunion Island since its inception. It is part of a particular employment situation: the unemployment rate is very high, especially among young people, who are encouraged to leave the island to receive training or find jobs. According to insertion counselors, civic service is exploited by young people, who use it to earn an income. A long-term survey, based on observations in associations and interviews with volunteers in 2015, 2016 and 2021, reveals strategies used by young people to establish themselves socially and professionally, who "juggle” with different public measures in order to find stable work.